COMPARATIVE EVALUATION OF HYPERBARIC BUPIVACAINE AND LEVOBUPIVACAINE AS SPINAL ANESTHESIA AGENTS IN FEMALES UNDERGOING CESAREAN SECTION: A CLINICAL STUDY. - Jagannath Panda; Ratikanta Nayak; Susanta Kumar Behera (Student's Journal of Health Research, 2023)
Background: Obstetric anesthesia procedures must achieve appropriate muscular relaxation and enough analgesia with not too few side effects on the mother or fetus due to the anesthetic drug utilized. The purpose of the current study was to compare the clinical outcomes of lower-segment cesarean section (LSCS) patients who received hyperbaric bupivacaine with levobupivacaine as a spinal anesthetic agent. Materials and methods: The research study included 240 pregnant women in the American Society of Anesthesiologists (ASA) I-II groups who were scheduled to undergo elective cesarean operations. Two groups of patients were randomly assigned. It took 2.3 cc to administer the mixtures of 10 mg levobupivacaine (0.5%) + 15 cg fentanyl for Group L (n = 60) patients, and 10 mg hyperbaric bupivacaine (0.5%) + 15 cg fentanyl for B (n = 60) patients. Pinprick and Bromage scales were used to evaluate the sensory and motor block features of the groups and side effects and observed hemodynamic alterations were noted. Results: It turned out that Group B had considerably longer times to achieve the maximal dermatome for the sensory block, to regress by two dermatomes, and to regress to the T12 dermatome. It was shown that Group B's motor block evolution progressed more quickly and lasted longer. While hypotension, bradycardia, and nausea were less common in Group L, Group B required more ephedrine (p<0.05). Conclusion: Levobupivacaine and fentanyl together can be a suitable choice for cesarean sections since the motor block time is shorter, the adverse effects of hypotension, bradycardia, and nausea are less common, and it maintains hemodynamic stability at higher sensory block levels.